Case report: A unique quadruple coexisting anomaly—scimitar syndrome, atrial septal defect, vascular ring, and pulmonary sequestration - Gładki, Marcin; Bednarek, Paweł R.; Owecki, Wojciech (Frontiers in Pediatrics, 2023)
The article describes a successful clinical outcome in the case of a 5-month old female with a diagnosis of incomplete vascular ring of aberrant right subclavian artery and ostium secundum atrial septal defect associated with partial anomalous pulmonary venous return of scimitar syndrome type, coexisting with right pulmonary sequestration. During hospitalization, surgical correction of the heart defect and resection of the lung sequestration were performed. To the best of our knowledge, described constellation of defects is a unique phenomenon, posing a challenge for complex treatment and disease management.